Cross-Talk Between Sporophyte and Gametophyte Generations Is Promoted by CHD3 Chromatin Remodelers in Arabidopsis thaliana. Issue 2 (1st June 2016) - Carter, Benjamin; Henderson, James T; Svedin, Elisabeth; Fiers, Martijn; McCarthy, Kyle; Smith, Amanda; Guo, Changhua; Bishop, Brett; Zhang, Heng; Riksen, Tjitske; Shockley, Allison; Dilkes, Brian P; et al.
Abstract: Angiosperm reproduction requires the integrated development of multiple tissues with different genotypes. To achieve successful fertilization, the haploid female gametophytes and diploid ovary must coordinate their development, after which the male gametes must navigate through the maternal sporophytic tissues to reach the female gametes. After fertilization, seed development requires coordinated development of the maternal diploid integuments, the triploid endosperm, and the diploid zygote. Transcription and signaling factors contribute to communication between these tissues, and roles for epigenetic regulation have been described for some of these processes. Here we identify a broad role for CHD3 chromatin remodelers in Arabidopsis thaliana reproductive development. Plants lacking the CHD3 remodeler, PICKLE, exhibit various reproductive defects including abnormal development of the integuments, female gametophyte, and pollen tube, as well as delayed progression of ovule and embryo development. Genetic analyses demonstrate that these phenotypes result from loss of PICKLE in the maternal sporophyte. The paralogous gene PICKLE RELATED 2 is preferentially expressed in the endosperm and acts antagonistically with respect to PICKLE in the seed: loss of PICKLE RELATED 2 suppresses the large seed phenotype of pickle seeds. Surprisingly, the alteration of seed size in pickle plants is sufficient to determine the expression of embryonic traits in the seedling primary root. These findings establish an important role for CHD3 remodelers in plant reproduction and highlight how the epigenetic status of one tissue can impact the development of genetically distinct tissues.